PENGGUNAAN MEDIA PEMBELAJARAN PAPAN JURANG PADA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SDI MAUMERE - Elisabeth Meti; Desi Maria El puang; Hermus Hero (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of low learning outcomes of class II students of SDI Maumere who have difficulty in understanding the concept of addition and subtraction. Most students have not been able to understand the concept of addition and subtraction. The purpose of this study is to determine the learning outcomes of class II students of SDI Maumere, addition and subtraction material using the cliff board media. This research method uses classroom action research based on lesson study with plan-do-see stages. The subjects of this study were class II students of SDI Maumere, totaling 27 people with 15 boys and 12 girls. Data collection techniques used observation and tests with instruments in the form of learning observation sheets in lesson study activities, student activity observation sheets, and lesson study stage assessment sheets. The results of the study showed that in cycle 1 the assessment results at the lesson study stage were 89.47; The results of student activity observations were 65.7% and the test scores of 27 students were known to have 12 (47%) students who completed and 5 (53%) students who did not complete. In cycle 2, the results of the lesson study stage were 92%, the results of student activity observations were 93% and the test scores of 27 students were 22 (79%) students who completed and 5 (21%) students who did not. This indicates an increase in student learning outcomes. So it is concluded that using the ravine board media can improve student learning outcomes in addition and subtraction material for class II SDI Maumere.